Increased risk of stroke in patients with diffuse idiopathic skeletal hyperostosis: a nationwide population-based cohort study - Cheng, Yuan-Yang; Lin, Ching-Heng; Tsai, Po-Yi; Chen, Yi-Huei; Lin, Shih-Yi; Chang, Shin-Tsu (Scientific reports, 2021)
Diffuse idiopathic skeletal hyperostosis (DISH) is frequently an incidental finding during X-ray examination. Although it has been shown to be associated with several chronic diseases, the hazard of cerebrovascular disease has seldom been explored. Our study aimed at determining the risk of stroke conferred by DISH, which is a retrospective cohort study adopting the largest medical database in Taiwan. Patients with a diagnosis of DISH at least three times from 2005 to 2010 were identified as the study group, and those in the control group were selected by matching age and gender. Patients were followed up until the end of 2015 to trace the incidence of stroke. Cox regression analysis was performed to compute the hazard ratio of stroke. Among the included 5300 patients, 1060 had a diagnosis of DISH. Significantly higher prevalence rates of stroke, hypertension, diabetes, and hyperlipidemia were noted in these patients. Overall, DISH conferred a 1.68 times higher risk of developing stroke. The significantly higher hazard ratio could be identified in both genders whether hypertension existed or not. Even in those without comorbidities, DISH still conferred a significantly higher risk of cerebrovascular disease in the future, which should never be ignored when encountered during clinical practice.